Prediction of Electroconvulsive Therapy Response and Remission in Major Depression: Meta-analysis – CORRIGENDUM. (3rd April 2018) - van Diermen, Linda; van den Ameele, Seline; Kamperman, Astrid M.; Sabbe, Bernard C.G.; Vermeulen, Tom; Schrijvers, Didier; Birkenhäger, Tom K.
Summary: This notice describes a correction to the above mentioned paper.